‘Allāl al-Fāsī and Sahal Mahfudh: Maqāṣid asy-Sharī’a as the Meeting Point of the Different Inclinations Rooted in Sunni Tradition - Muhammad Nashrul Haqqi; Shofaussamawati Shofaussamawati (LPPM IAIN Kudus, 2023)
This article aims to highlight the position of 'Allāl and Sahal in the development of Maqāṣid al-Syar'a theory and its application to political, social, and economic problems. The approach is carried out by examining their intellectual career background, examining the theory of the development of Maqāṣid al-Syar'a theory and how they implement it. As a result, 'Allal and Sahal took different positions about Maqāṣid al-Syar'a, although in the and they produced similar or almost the same legal opinions. They both propose a democratic government, an economy that prioritizes the interests of the community, and social conditions that prioritize the interests of women. The dominant difference lies in the characteristics of the choice of sources that indicate affiliation. ' Allāl more often refers to the Qur'an and Sunnah as recommended by the Salafis. While Sahal more often refers to the fiqh tradition advocated by traditional schools, by accommodating modern theories, such as philosophy and social sciences. At this point, the author argues that the concept of Maqāṣid al-Syar'a is a meeting point for various tendencies rooted in the Sunni intellectual tradition, including the different tendencies espoused by 'Allāl and Sahal.